2020
DOI: 10.5194/amt-13-3923-2020
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric ammonia (NH<sub>3</sub>) over the Paris megacity: 9 years of total column observations from ground-based infrared remote sensing

Abstract: Abstract. In this paper, we present the first multiyear time series of atmospheric ammonia (NH3) ground-based measurements in the Paris region (Créteil, 48.79∘ N, 2.44∘ E, France) retrieved with the midresolution “Observations of the Atmosphere by Solar absorption Infrared Spectroscopy” (OASIS) ground-based Fourier transform infrared solar observatory. Located in an urban region, OASIS has previously been used for monitoring air quality (tropospheric ozone and carbon monoxide) thanks to its specific column sen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 52 publications
2
20
0
Order By: Relevance
“…showed a correlation of r = 0.79 and slope = 0.73. The same study also found that the FTIR in Paris is capable of providing information about NH 3 variability at a "regional" scale (∼ 120 km) Tournadre et al (2020). Although not quantified in this study, the line-of-sight through the atmosphere (which changes throughout the day) may also affect the representative scale of ground-based solar-pointing FTIR observations.…”
mentioning
confidence: 67%
“…showed a correlation of r = 0.79 and slope = 0.73. The same study also found that the FTIR in Paris is capable of providing information about NH 3 variability at a "regional" scale (∼ 120 km) Tournadre et al (2020). Although not quantified in this study, the line-of-sight through the atmosphere (which changes throughout the day) may also affect the representative scale of ground-based solar-pointing FTIR observations.…”
mentioning
confidence: 67%
“…Consequently, containment measures implemented in various countries have shown changes in the air quality [11][12][13][14]. The use of fossil fuels by road vehicles is the main source of four groups of pollutants, including GHG [10], including carbon dioxide (CO 2 ), methane (CH 4 ), and nitrous oxide (N 2 O); ozone precursor gases, such as carbon monoxide (CO) [15], non-methane volatile organic compounds (NMVOC) [16], and nitrogen oxides (NOx) [17,18]; aerosols, including black carbon (BC) [10] and particulate matter (PM 2.5, PM 10 ) [15]; acidifying gases, such as ammonia (NH 3 ) [19] and sulfur dioxide (SO 2 ) [20]. GHG emissions, such as CO 2 , are mainly produced by power generation and road transport.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, one of the main anthropogenic emissions sources of BC is the incomplete combustion of fossil fuels (especially diesel) in vehicles [10]. Acidifying gases are emitted by the combustion of biomass and fossil fuels as well as by industrial activity [19,20]. NH 3 emissions related to road traffic are due to use of catalytic NOx reduction systems on light and heavy-duty vehicles [19], whose devices use an injection of urea or ammonia [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Hu et al (2014) investigating NH 3 in downtown Toronto has shown that greenery within the city, where chemical fertilizers are commonly used, is an important source of NH 3 when temperatures are above freezing and that potential sources at temperatures below freezing have yet to be investigated. Additionally, recent studies have shown the increased capacity for satellitebased instruments to measure spatial and temporal distributions of NH 3 total columns at global (Van Damme et al, 2014a;Warner et al, 2016;Shephard et al, 2020), regional (Van Damme et al, 2014b;Warner et al, 2017;Viatte et al, 2020), and point-source scales (Van Damme et al, 2018;Clarisse et al, 2019a;Dammers et al, 2019).…”
Section: Introductionmentioning
confidence: 99%